The Identity of the Main Character in Life of Pi novel by Yann Martel (Psychology of Literature) - Sahril, Mohamad (ENGLISH JOURNAL, 2016)
The objective of this research was to understand comprehensively the identity of the main character in the novel "Life of Pi" by Yann Martel. It was a qualitative research with content analysis conducted in Jakarta, from June to August 2013. The data were collected through comprehensive reading to the novel, some relevant books, and articles review in internet. Then, it was analyzed through the psycho-analysis theory. Since this is a qualitative research and the researcher himself is the instrument, most of activities were conducted by the study of literature. It was done by tracing relevant data in novels which showed the developmental phases of the main character from childhood to his teenage in order to know his personality, conflicts, the factors which affect the search for identity, and the efforts made by the main character in his search of identity. Results of this research showed that the main character in the novel Life of Pi by Yann Martel is extrovert, intelligent, earnest and energetic. He is a devout adherent of three religions: Hinduism, Christianity, and Islam. He is also a lecturer at the University of Toronto, and an animal lover.